2020
DOI: 10.21203/rs.3.rs-42568/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wrist Tuberculosis-experience From Eighteen Cases: A Retrospective Study

Abstract: Background Wrist tuberculosis is a rare disease, easy to cause misdiagnosis, delay treatment and lead to poor prognosis. In this study, the clinical manifestations, diagnosis, treatment and prognosis of 18 cases of wrist tuberculosis were analyzed retrospectively. Methods We conducted a retrospective study investigating tuberculosis of the wrist, diagnosed in 18 patients from August 2013 to November 2018. Puncture biopsy confirmed the diagnosis. The study includes 11 males and 7 females, and 8 left and 10 ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Ely LW [4] firstly reported surgical treatment of wrist TB in 1920, two cases of wrist TB were successfully treated by radical debridement and spontaneous wrist arthrodesis with "rod" shaped tibial grafting and postoperative immobilization using plaster of Paris. Due to its rarity, studies on the treatment outcome have been rarely reported [5][6][7][8][9][10]. Surgical treatment is varied based on the involvement of bone, joint, and synovium, severity of the bony destruction, influence of hand/wrist function, and the effect on the patient's daily life, which include radical debridement of the lesion with or without bone grafting and immobilization using casting, plate fixation or external fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Ely LW [4] firstly reported surgical treatment of wrist TB in 1920, two cases of wrist TB were successfully treated by radical debridement and spontaneous wrist arthrodesis with "rod" shaped tibial grafting and postoperative immobilization using plaster of Paris. Due to its rarity, studies on the treatment outcome have been rarely reported [5][6][7][8][9][10]. Surgical treatment is varied based on the involvement of bone, joint, and synovium, severity of the bony destruction, influence of hand/wrist function, and the effect on the patient's daily life, which include radical debridement of the lesion with or without bone grafting and immobilization using casting, plate fixation or external fixation.…”
Section: Introductionmentioning
confidence: 99%